ANALYSIS AND DESIGN OF A NEW STRUCTURE FOR 10-BIT 350MS/S PIPELINE ANALOG TO DIGITAL CONVERTER - Rezapour, Arash; Tavakoli, Mohammad Bagher; Setoudeh, Farbod (Gênero & Direito, 2019)
A 10-bit pipelined Analog to Digital converter is proposed in this paper with using 0.18 µm TSMC technology. In this paper, a new structure is proposed to increase the speed of the pipeline analog to digital convertor. So at the first stage is not used the amplifier and instead the buffer is used for data transfer to the second stage. The speed of this converter is 350MS/s. An amplifier circuit with accurate gain of 6 and a very accurate unit gain buffer circuit that are open loop with a new structure were. used. In this Converter, the first 3 bits are extracted simultaneously with sampling. The proposed analog-to-digital converter was designed with the total power consumption 75mW using power supply of 1.8v.